2021
DOI: 10.1099/jmm.0.001320
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a plasmid-borne tigecycline resistance in Klebsiella pneumoniae in Vietnam

Abstract: Tigecycline is a last-resort antimicrobial used to treat multidrug-resistant Gram-negative bacterial infections. One of the common antimicrobial resistance mechanisms is the efflux pump system composed of membrane protein complexes to excrete xenobiotic substrates. Recently, a novel gene cluster, tmexCD1-toprJ1, encoding the resistance–nodulation–cell division (RND) efflux pump was identified on plasmids in Klebsiella pneumoniae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Recently, mobile tigecycline resistance genes, tet(X3), tet(X4), and other variants, tet(X5) to tet(X14), encoding flavin-dependent monooxygenases that catalyze tigecycline degradation were emerged in Enterobacterales and Acinetobacter species in China and other countries[4][5][6] . Furthermore, a mobile tigecycline resistance gene cluster, tmexCD-toprJ, encoding the resistancenodulation-cell division (RND) efflux pump that excretes multiple antimicrobials, such as tetracyclines including tigecycline, cephalosporins, fluoroquinolones, and aminoglycosides, emerged predominantly in Enterobacterales: tmexCD1-toprJ1 was identified in plasmids in Klebsiella species isolated from humans and livestock in China and Vietnam[7][8][9] . tmexCD2-toprJ2 was identified in the plasmid and chromosome of Raoultella ornithinolytica isolated from a human in China 10 .A carbapenem-and tigecycline-resistant K. aerogenes isolate NUITM-VK5 was obtained from an urban drainage in Hanoi, Vietnam, in March 2021.…”
mentioning
confidence: 99%
“…Recently, mobile tigecycline resistance genes, tet(X3), tet(X4), and other variants, tet(X5) to tet(X14), encoding flavin-dependent monooxygenases that catalyze tigecycline degradation were emerged in Enterobacterales and Acinetobacter species in China and other countries[4][5][6] . Furthermore, a mobile tigecycline resistance gene cluster, tmexCD-toprJ, encoding the resistancenodulation-cell division (RND) efflux pump that excretes multiple antimicrobials, such as tetracyclines including tigecycline, cephalosporins, fluoroquinolones, and aminoglycosides, emerged predominantly in Enterobacterales: tmexCD1-toprJ1 was identified in plasmids in Klebsiella species isolated from humans and livestock in China and Vietnam[7][8][9] . tmexCD2-toprJ2 was identified in the plasmid and chromosome of Raoultella ornithinolytica isolated from a human in China 10 .A carbapenem-and tigecycline-resistant K. aerogenes isolate NUITM-VK5 was obtained from an urban drainage in Hanoi, Vietnam, in March 2021.…”
mentioning
confidence: 99%
“…FN396876 ) and tet (X) (accession no. MK134376 ) and purified genomic DNA from tmexCD1-toprJ1 -harboring Klebsiella pneumoniae strain MH15-269M ( 9 ) were used as positive controls. Purified water was used as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, variants of a mobile tigecycline resistance gene, tet (X), encoding flavin-dependent monooxygenases that catalyze tigecycline degradation, emerged in Enterobacterales and Acinetobacter species in China and other countries ( 4 6 ). Furthermore, a mobile tigecycline resistance gene cluster, tmexCD-toprJ , encoding the resistance-nodulation-cell division (RND) efflux pump that excretes multiple antimicrobials, such as tetracyclines including tigecycline, cephalosporins, fluoroquinolones, and aminoglycosides, emerged predominantly in Enterobacterales : tmexCD1-toprJ1 was identified in plasmids in Klebsiella species isolated from humans and livestock in China and Vietnam ( 7 9 ). tmexCD2-toprJ2 was identified in the plasmid and chromosome of Raoultella ornithinolytica isolated from a human in China ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…This gene cluster was first identified in animal isolates but soon later was also found in clinical isolates (Sun et al, 2020). TmexCD1-ToprJ1 was initially reported in China, but it has now been found in clinical K. pneumoniae isolates outside of China (Hirabayashi et al, 2021), suggesting this resistance has started to spread into other global regions. Two homologous variants, TmexCD2-ToprJ2 (Wang et al, 2021a) and TmexCD3-ToprJ3 (Wang et al, 2021b), have also been identified in Raoultella ornithinolytica and Proteus mirabilis, displaying similar tigecycline resistance profiles.…”
Section: Introductionmentioning
confidence: 93%